2001
DOI: 10.1242/dev.128.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Wnt receptor gene Fzd5 is essential for yolk sac and placental angiogenesis

Abstract: Wnts are secreted signaling molecules implicated in various developmental processes and frizzled proteins are the receptors for these Wnt ligands. To investigate the physiological roles of frizzled proteins, we isolated and characterized a novel mouse frizzled gene Fzd5. Fzd5 mRNA was expressed in the yolk sac, eye and lung bud at 9.5 days post coitum. Fzd5 specifically synergized with Wnt2, Wnt5a and Wnt10b in ectopic axis induction assays in Xenopus embryos. Using homologous recombination in embryonic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…FZD 5 has been reported to interact with WNT-2, WNT-3, WNT-3A, WNT-5A, WNT-7A, WNT-7B, WNT-9B, WNT-10B, and WNT-11 in various cellular and developmental contexts, leading to numerous cellular outcomes that still require careful characterization at the molecular level (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Loss-of-function studies have revealed a role for FZD 5 in ocular development, whereas gain-of-function studies have demonstrated its role in synaptogenesis (11,16).…”
Section: Introductionmentioning
confidence: 99%
“…FZD 5 has been reported to interact with WNT-2, WNT-3, WNT-3A, WNT-5A, WNT-7A, WNT-7B, WNT-9B, WNT-10B, and WNT-11 in various cellular and developmental contexts, leading to numerous cellular outcomes that still require careful characterization at the molecular level (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Loss-of-function studies have revealed a role for FZD 5 in ocular development, whereas gain-of-function studies have demonstrated its role in synaptogenesis (11,16).…”
Section: Introductionmentioning
confidence: 99%
“…Although LRP5 protein is higher in unfractionated stromal cells than eMSC, FZD5 and LRP5 have coexpression in a significant proportion of the eMSC population, suggesting the possibility of FZD5-LRP5 interaction in eMSC maintenance. FZD5 is a common noncanonical WNT receptor (Ishikawa et al, 2001;Arderiu et al, 2014;Kim et al, 2019), and the blocking of WNT5A-FZD5 signaling pathway can inhibit the PKC pathway (Weeraratna et al, 2002). A recent study has demonstrated FZD5 as a regulator in the maintenance of human mesenchymal stem/ stromal cells (hMSCs) (Harada et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…FZD5 is a common noncanonical WNT receptor ( Ishikawa et al, 2001 ; Arderiu et al, 2014 ; Kim et al, 2019 ), and the blocking of WNT5A–FZD5 signaling pathway can inhibit the PKC pathway ( Weeraratna et al, 2002 ). A recent study has demonstrated FZD5 as a regulator in the maintenance of human mesenchymal stem/stromal cells (hMSCs) ( Harada et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The highly conserved Wnt signaling axes regulate cell differentiation, apoptosis, and orientation. Deficiency in the Wnt receptor Frizzled-5 is embryonically lethal, as it severely impairs yolk sac angiogenesis [82] . Wnt3a promotes SMC differentiation by upregulating SM22-α in vitro [83] .…”
Section: Major Signaling Pathways Involved In Vsmc Developmentmentioning
confidence: 99%
“…Deficiency in the Wnt receptor Frizzled-5 is embryonically lethal, as it severely impairs yolk sac angiogenesis. [82] Wnt3a promotes SMC differentiation by upregulating SM22-a in vitro. [83] Wnt7b is essential for pulmonary vascular smooth muscle integrity.…”
Section: Wnt Signalingmentioning
confidence: 99%